ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IPM DI DKI JAKARTA PADA TAHUN 2016-2020 - Pradana, Oktarizain Dida; Juliannisa, Indri Arrafi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
The Human Development Index is an index that measures the success of local development in terms of education, health and well-being. The purpose of this study was to investigate the impact of public expenditure surveys. state health care expenditure number of schools number of hospitals and number of poor 6 in the Jakarta DKI City and Municipal Human Development Index. Use written search as the research method. Secondary quantitative data were used in the publication of Statistics Finland in 2016–2020. Cluster regression was used in this study. government education expenditure on government health care spending and the number of hospitals that have a significant impact on human development and the number of schools and poor people that have no impact on human development, DKI Jakarta Index.